ANALYSIS OF TEACHERS' PEDGOGIC COMPETENCE IN DEVELOPING ISLAMIC RELIGIOUS EDUCATION LEARNING DESIGNS BASED ON SCIENTIFIC LEARNING APPROACHES - Sukarno, Muhd.; Prasojo, Zaenuddin Hudi; Wahab, Wahab (Jurnal Konseling Pendidikan Islam, 2023)
Research aims to determine the pedagogical competence of PAI teachers at SDN 1 Nanga Pinoh, SMPN 2 Nanga Pinoh, and SMAN 1 Nanga Pinoh, Melawi Regency, in developing the design of a learning implementation plan in PAI subjects based on a scientific learning approach based on the Development Guidebook and Sample Plans Implementation of Islamic Religious Education Learning and High School Characteristics Curriculum 2013, issued by the Ministry of Religion of the Republic of Indonesia. This research uses a qualitative-descriptive approach, where the research data is presented in a narrative form with the type of case study research. Data collection techniques using documentation, observation, and interview techniques While the data analysis technique used is content analysis. The results of the study show that the pedagogic competence of Islamic Religious Education teachers at three school levels in developing the design of learning implementation plans for Islamic Education subjects is based on a scientific learning approach. This also indicates that PAI teachers at SMAN 1 Nanga Pinoh have pedagogical skills.